Apparent Inhibition of Chloroplast Protein Import by Cold Temperatures Is Due to Energetic Considerations Not Membrane Fluidity. - Leheny, E. A. (1994)
The transport of proteins across virtually all types of biological membranes has been reported to be inhibited by low temperatures. Paradoxically, plants are able to acclimate to growth at temperatures below which protein import into chloroplasts is known to be blocked. In examining this incongruity, we made a number of unexpected observations. First, chloroplasts isolated from plants grown at 7/1[deg]C in light/dark and from plants grown at 25[deg]C were able to import proteins with the same efficiency over a temperature range from 5 to 21[deg]C, indicating that no functional adaptation had taken place in the protein import machinery of chloroplasts in these cold-grown plants. Second, chloroplasts from warm-grown plants were able to take up proteins at temperatures as low as 4[deg]C provided that they were illuminated. We determined that light mediates the import process at 5[deg]C by driving ATP synthesis in the stroma, the site of its utilization during protein transport. Direct measurement of the envelope phase transition temperature as well as the activity of the ATP/ADP translocator in the inner envelope membrane at 5 and 25[deg]C demonstrated that the cold block of protein import into chloroplasts observed in vitro is due primarily to energetic considerations and not to decreased membrane fluidity.